The Author's View on the Anthology of Short Stories Tukar Takdir by Valiant Budi for the Utilization of Literary Learning - Qonita Sumardani; Ani Rakhmawati; Atikah Anindyarini (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This research is motivated by the limited use of literary works, especially short story anthologies, as a medium for revealing the author's worldview in the context of literary learning. The focus of this research is the short story anthology Tukar Takdir by Valiant Budi, which is considered representative of contemporary Indonesian society's collective consciousness. The purpose of this research is to describe the author's worldview in the anthology by examining the story structure, character conflicts, and cultural symbols used. This research uses a qualitative descriptive method, with data collected through document analysis, observation, and interviews, and validity is established through theoretical triangulation. Data analysis is carried out using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and result verification. The main data of this research are the texts of the short stories in Tukar Takdir and supporting documentation from the author and readers. The results of this research show that the author's worldview is reflected in the character conflicts and the storyline that depicts the dialectic between individual fate and social structure. This finding confirms that literary works are not only aesthetic but also represent ideology and social awareness, serving as a medium for critical learning. In conclusion, Tukar Takdir is not just an anthology of short stories but rather a representation of the author's worldview, relevant to contemporary social problems, and with great potential to support reflective, dialogical, and transformative literary learning.